ANALISIS BAURAN PEMASARAN PROMOSI DAN TEMPAT DALAM MENINGKATKAN PENJUALAN PRODUK HERBAL HPA - Kristanto Ardi; Warneri Warneri; Okianna Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractTwo main marketing objectives are attracting new customers by promising superior valueand retaining current customers by providing satisfaction. The general problem that is tryingto be lifted in this research is "how to analyze promotion and marketing mix of places inincreasing sales of HPA Pontianak Herbal products". The method used in this study is a casestudy method with a form of qualitative research. Based on the results of the study througha 5-respondent interview answer and also based on observations that the HPA promotionmix of product sales is implementing advertising media in the form of outdoor media andlower-line media. Sales promotion Apply Customer promotion, trade promotion, businesspromotion. Personal sales are also applied with face-to-face sales. Public relations are alsoimplemented, and direct marketing is implemented through online and offline stores. HPAlocation analysis of product sales has no official centralized location in Pontianak, while thetype of distribution channel used HPA There are two, first producers-stockist/Distributor-member/Reseller-member/consumer, and both manufacturers/ Company-Stokis/Distributor-member/consumer.Keywords: Analysis, Promotion mix, Place mix, Product sales